Her deal with the Greek devil - Crews, Caitlin (Crews, Caitlin. Rich, ruthless & Greek., 2021)
"Constantine Skalas may seem idle and arrogant, but he hides a razor-sharp need for vengeance against the Payne family. The key? His former stepsister, Molly, who's blossomed from ugly duckling into gorgeous supermodel. Constantine will offer her a perfectly outrageous proposition... Virgin Molly knows the danger of walking into a powerful man's den. Yet only a deal with the devil himself will save her beloved mother from bankruptcy. Constantine has always been sinfully seductive, but now, bound by their pact, Molly burns for him. And there's no going back..."--